The Wapping Baptists: Murky Origins and the Silence of John Spilsbery - Sherman, Nathan (Baptist quarterly, 2024)
The Wapping Baptist church has often been referred to as the oldest Baptist church in London. Historians have confidently placed its origins as early as 1633 when a small group of those adopting believer’s baptism departed from the semi-separatist Jacob-Lathrop-Jessey church, then soon to be pastored by the influential John Spilsbery. However, there is no primary source evidence connecting those of this early exodus to the later Wapping Baptists, and similarly, there is no evidence to suggest that Spilsbery was ever at Wapping (the first suggestion not appearing until 1808). This article will not, unfortunately, clarify the Wapping church origins – they remain murky and obscure – however, it will raise doubt surrounding the traditional narrative.